2014
DOI: 10.1021/am505024p
|View full text |Cite
|
Sign up to set email alerts
|

Design of Antimicrobial Membrane Based on Polymer Colloids/Multiwall Carbon Nanotubes Hybrid Material with Silver Nanoparticles

Abstract: The aim of this study was to obtain membranes with antimicrobial activity presenting a complex sandwich-type structure. The outer layers are comprised of poly(methyl methacrylate) membranes, whereas the inner active layer consists of a modified commercial membrane to achieve antimicrobial properties. This activity arises due to the presence of silver nanoparticles in a material with a hybrid composition deposited on a commercial membrane. This hybrid material consists of polymer colloids and multiwall carbon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Figure shows the RAMAN spectra of both pristine and epoxy‐functionalized MWCNTs. This spectroscopy analysis revealed that the I D / I G ratio increased from 1.277 to 1.37, confirming the successful functionalization of the MWCNTs without damaging the carbon nanotube structure …”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Figure shows the RAMAN spectra of both pristine and epoxy‐functionalized MWCNTs. This spectroscopy analysis revealed that the I D / I G ratio increased from 1.277 to 1.37, confirming the successful functionalization of the MWCNTs without damaging the carbon nanotube structure …”
Section: Resultsmentioning
confidence: 52%
“…This spectroscopy analysis revealed that the I D /I G ratio increased from 1.277 to 1.37, confirming the successful functionalization of the MWCNTs without damaging the carbon nanotube structure. [35][36][37] The degree of functionalization of the MWCNTs is very important; therefore, they have also employed TGA for the materials characterization. The weight loss in the case of the epoxyfunctionalized MWCNTs started at 140-150 8C and ended at approximately 370 8C and the maximum degradation temperature T max was registered around 278 8C (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The highest obtained value (92°CA) was exactly on the edge of the hydrophilic and hydrophobic surfaces, which still offers a certain versatility of the membrane applications. This kind of versatility, next to the potential antibacterial effect of the copper ions trapped on the membrane surface could be the basis of reusing such membranes in biowaste separation (Rusen et al, 2014).…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
“…Furthermore, incorporation of pristine carbon nanotubes (CNTs) or graphene oxide (GO) at certain concentrations into the polymer matrix proved to be an advantageous alternative to realize filtration membranes with improved hydrophilicity, thermal stability, and water flux permeability without damaging the mechanical properties of the hybrid membranes [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%